High glucose induces podocyte ferroptosis through BAP1/SLC7A11 pathway - Ren Peiyao; Man Xueli; Sun Wenbo; Zheng Danna; Gong Jianguang; Jin Juan; He Qiang (Heliyon)
Background: Ferroptosis plays an important role in the development of diabetic nephropathy (DN). However, its specific regulatory mechanisms remain unclear. Methods: MPC5 cells were cultured in high glucose (HG) medium to stimulate the HG environment in vitro. Ferroptosis and oxidative stress were assessed by measuring malondialdehyde (MDA) levels, cystine uptake capacity, and reactive oxygen species (ROS). C91A and wild type (WT) MPC5 cells were constructed to further explore the specific regulatory mechanism of BAP1 on SLC7A11. Results: Erastin-induced ferroptosis was sensitized by HG, leading to a significant reduction in glutathione (GSH) levels, increased oxidative stress, and inhibited cystine uptake in podocytes. HG suppressed the expression of SLC7A11. Overexpression of SLC7A11 improved cystine uptake and reduced oxidative stress. Furthermore, HG increased BAP1 levels. Silencing BAP1 up-regulated SLC7A11 and mitigated ferroptosis. Cell proliferation was reduced after SLC7A11 knockdown. In BAP1 WT cells, but not in its C91A mutant cells, the transcription of SLC7A11 was downregulated and the level of ferroptosis was increased. Conclusion: HG inhibits cystine uptake in podocytes by promoting the expression of BAP1 and inhibiting H2Aub deubiquitination on SLC7A11, leading to lipid peroxide accumulation and ferroptosis in podocytes.